PENGARUH PENDIDIKAN, INVESTASI ASING LANGSUNG DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI ASEAN - Rima Melani; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study research  determine the effect of (1) Education on Economic Growth on ASEAN countries, (2) Foreign Direct Investment on Economic Growth on ASEAN countries (3) Labor on Economic Growth in ASEAN countriess using the method of multiple linear equations with the Least Square Panel Model using panel data from 2012 to 2017. Results of estimation from multiplier linear equation shows that (1) education has a possitive significant  effect on economics growth in ASEAN countries (2) Foreign Direct Investment has a possitive significant  on economic growth on ASEAN countries and 3) Labor has a possitive significant effect on Economic Growth on ASEAN  countries.